Analysis of RPA190 revealed multiple positively selected mutations associated with metalaxyl resistance in Phytophthora infestans. Issue 8 (30th March 2018) - Chen, Fengping; Zhou, Qian; Xi, Jing; Li, Dong‐liang; Schnabel, Guido; Zhan, Jiasui
Abstract: BACKGROUND: Metalaxyl is a phenylamide fungicide, introduced for oomycete management in the 1970s. RPA190 gene has been reported to be associated with metalaxyl resistance, although other genes may also be involved in the process. This study assessed the evolutionary association of amino acid (AA) mutations in RPA190 with metalaxyl resistance in Phytophthora infestans . RESULTS: All isolates from Yunnan were resistant to metalaxyl with multiple AA mutations in RPA190 . Two main evolutionary pathways were found in metalaxyl resistance: in one pathway, RPA190 from sensitive isolates (SAA) underwent a single type AA mutation at position 1476, changing from valine to glycine (V1476G); the second pathway involved multiple steps of point mutations. In a phylogenetic tree, nucleotide sequences of the gene clustered into six clades largely corresponding to AA isoform groups. Among the clusters, sequences carrying mutations V1476G and P980S formed two independent clades; other clades shared a common mutation of F382Y. All three mutations together with another two were shown to be under positive selection and the number of AA mutations in an isolate was positively correlated with EC50 values. CONCLUSION: Multiple mutations such as V1476G, P980S, and F382Y in RPA190 contribute to metalaxyl resistance, and resistance to metalaxyl can emerge in at least two independent pathways in P. infestans . © 2018 Society of Chemical Industry Abstract : The study assessed the evolutionary association of amino acid mutations in RPA190 with metalaxyl resistance in Phytophthora infestans .